Dairy industry state support measures: issues and foreign experience (Journal of Economic Research & Business Administration, 2016)
This article presents and analyzes the experience of state support of agriculture in Europe, the United States, the Republic of Belarus and the Russian Federation and is intended to determine the goals and directions of development of agrarian and industrial complex in terms of the state’s response to changes in the macro environment. Every state is interested in the development of the dairy industry, as dairy products are of strategic importance in ensuring its food security. Therefore, countries strongly sup- port its farmers, milk producers and companies producing milk as a fin- ished product by issuing grants and subsidies to ensure their competitive- ness in domestic and global markets. Thus, market relations in agriculture are intertwined with government regulation.
Keywords: government support; government programs; dairy industry; change management